Implementation of Blended Learning Model Using the Schoology Application - Virdinarti Putra, Lisa; Yulfani, Siswi (KnE Social Sciences, 2022)
Implementing blended learning requires media facilitating various online learning tools, one of which is Schoology. Opening extensive learning resources for students allows teachers to switch from teacher-centred learning to student-centred learning. Schoology is a learning management system that allows teachers to interact with students through various interesting features. Teachers can display teaching materials, discussions through questions and answers, and collection of assignments. Mathematics, a subject that requires various graphic illustrations, diagrams, and visualizations, is very suitable to be taught through Schoology. Teachers can help students understand various mathematical concepts by taking advantage of the various learning features provided by Schoology. Schoology allows communication between teachers and students to be more interactive because the platform is similar to social media. Teachers can create virtual classes to carry out online learning at home so that students are trained to act actively and independently in learning. Based on research and data analysis shows that there are differences in learning outcomes between students who use school learning media and students who use conventional methods, there is a positive and significant influence of Schoology learning media on learning outcomes, and there is a positive and significant influence on learning motivation on learning outcomes. Keywords: Blended Learning, Schoology, Mathematics, Teachers, and Students